ERROR ESTIMATION FOR A PIEZOELECTRIC CONTACT PROBLEM WITH WEAR AND LONG MEMORY - BACHIR DEHDA; MOHAMMED SALAH MESAI AOUN; ABDELAZIZ AZEB AHMED (International Journal of Applied Mathematics and Simulation, 2025)
We study a mathematical model for a quasistatic behavior of electro-viscoelastic materials. The problem is related to highly nonlinear and non-smooth phenomena like contact, friction and normal compliance with wear. Then, a fully discrete scheme is introduced based on the finite element method to approximate the spatial variable and the backward Euler scheme to discretize the time derivatives. For a numerical scheme, we prove the existence and uniqueness of the solutions, and derive optimal order error estimates under certain regularity assumption on the solution of the continuous problem. AMS subject classification. 35J85 · 49J40 · 47J20 · 74M15. REFERENCES [1] Aoun, M. S. M., Dehda, B., & Douib, B. (2024). Numerical study of a thermo-elasto-viscoplastic contact problem with adhesion using a hybrid method. Studies in Engineering and Exact Sciences, 5(2), e8308-e8308. Search in Google Scholar. https://doi.org/10.54021/seesv5n2-255 [2] Aoun, M. S. M., Selmani, M., & Ahmed, A. A. (2021). Variational analysis of a frictional contact problem with wear and damage. Mathematical Modelling and Analysis, 26(2), 170-187. Search in Google Scholar. https://doi.org/10.3846/mma.2021.11942 [3] Barboteu, M., Fernández, J. R., & Ouafik, Y. (2008). Numerical analysis of a frictionless viscoelastic piezoelectric contact problem. ESAIM: Mathematical Modelling and Numerical Analysis, 42(4), 667-682. Search in Google Scholar. https://doi.org/10.1051/m2an:2008022 [4] Barboteu, M., Fernández, J. R., & Tarraf, R. (2008). Numerical analysis of a dynamic piezoelectric contact problem arising in viscoelasticity. Computer methods in applied mechanics and engineering, 197(45-48), 3724-3732. Search in Google Scholar. https://doi.org/10.1016/j.cma.2008.02.023 [5] Batra, R. C., & Yang, J. (1995). Saint-Venant's principle in linear piezoelectricity. Journal of Elasticity, 38(2), 209-218. Search in Google Scholar. https://doi.org/10.1007/BF00042498 [6] Braess, D. (2001). Finite elements: Theory, fast solvers, and applications in solid mechanics. Cambridge University Press. Search in Google Scholar. https://doi.org/10.1017/CBO9780511618635 [7] Chau, O., Fernández, J. R., Shillor, M., & Sofonea, M. (2003). Variational and numerical analysis of a quasistatic viscoelastic contact problem with adhesion. Journal of Computational and Applied Mathematics, 159(2), 431-465. Search in Google Scholar. https://doi.org/10.1016/S0377-0427(03)00547-8. [8] Chau, O., Shillor, M., & Sofonea, M. (2004). Dynamic frictionless contact with adhesion. Zeitschrift für angewandte Mathematik und Physik ZAMP, 55, 32-47. Search in Google Scholar. https://doi.org/10.1007/s00033-003-1089-9 [9] Chau, O., & Oujja, R. (2015). Numerical treatment of a class of thermal contact problems. Mathematics and Computers in Simulation, 118, 163-176. Search in Google Scholar. https://doi.org/10.1016/j.matcom.2014.12.007 [10] Ciarlet, P. G. (1978). The finite element method for elliptic problems. Amsterdam: North-Holland Pub. Co.. Search in Google Scholar. https://lib.ugent.be/catalog/ebk01:1000000000549375 [11] Ciarlet, P. G. (1991). Basic error estimates for elliptic problems, Handbook of Numerical Analysis, Volume 2, Pages 17-351. Search in Google Scholar. https://doi.org/10.1016/S1570-8659(05)80039-0 [12] Fernández, J. R., Shillor, M., & Sofonea, M. (2003). Analysis and numerical simulations of a dynamic contact problem with adhesion. Mathematical and Computer Modelling, 37(12-13), 1317-1333. Search in Google Scholar. https://doi.org/10.1016/S0895-7177(03)90043-4 [13] Han, W., Shillor, M., & Sofonea, M. (2001). Variational and numerical analysis of a quasistatic viscoelastic problem with normal compliance, friction and damage. Journal of Computational and Applied Mathematics, 137(2), 377-398. Search in Google Scholar. https://doi.org/10.1016/S0377-0427(00)00707-X [14] Han, W., & Sofonea, M. (2007). On a dynamic contact problem for elastic-visco-plastic materials. Applied numerical mathematics, 57(5-7), 498-509. Search in Google Scholar. https://doi.org/10.1016/j.apnum.2006.07.003 [15] Han, W., Sofonea, M., & Kazmi, K. (2007). Analysis and numerical solution of a frictionless contact problem for electro-elastic–visco-plastic materials. Computer methods in applied mechanics and engineering, 196(37-40), 3915-3926. Search in Google Scholar. https://doi.org/10.1016/j.cma.2006.10.051 [16] Ikeda, T. (1996). Fundamentals of piezoelectricity. Oxford university press. Search in Google Scholar. https://doi.org/10.1524/zkri.1992.199.1-2.158 [17] Lerguet, Z., Shillor, M., & Sofonea, M. (2007). A frictional contact problem for an electro-viscoelastic body. Electronic Journal of Differential Equations (EJDE)[electronic only], 2007, Paper-No. Search in Google Scholar. https://ejde.math.txstate.edu/Volumes/2007/170/abstr.html [18] Maanani, A. A., Maanani, Y., Betka, A., & Benguessoum, A. (2024). PV-Battery hybrid system power management based on backstepping control. International Journal of Applied Mathematics and Simulation, 1(2). Search in Google Scholar. https://doi.org/10.69717/ijams.v1.i2.102 [19] Maceri, F., & Bisegna, P. (1998). The unilateral frictionless contact of a piezoelectric body with a rigid support. Mathematical and Computer Modelling, 28(4-8), 19-28. Search in Google Scholar. https://doi.org/10.1016/S0895-7177(98)00105-8 [20] Migórski, S. (2006). Hemivariational inequality for a frictional contact problem inelasto-piezoelectricity. Discrete and Continuous Dynamical Systems-B, 6(6), 1339-1356. Search in Google Scholar. https://doi.org/10.3934/dcdsb.2006.6.1339. [21] Migórski, S., Ochal, A., & Sofonea, M. (2011). Analysis of a quasistatic contact problem for piezoelectric materials. Journal of mathematical analysis and applications, 382(2), 701-713. Search in Google Scholar. https://doi.org/10.1016/j.jmaa.2011.04.082 [22] Moumen, L., & Rebiai, S. E. (2024). Stabilization of the transmission Schrodinger equation with boundary time-varying delay. International Journal of Applied Mathematics and Simulation, 1(1). Search in Google Scholar. https://doi.org/10.69717/ijams.v1.i1.95 [23] Selmani, M. (2013). Frictional contact problem with wear for electro-viscoelastic materials with long memory. Bulletin of the Belgian Mathematical Society-Simon Stevin, 20(3), 461-479. Search in Google Scholar. https://doi.org/10.36045/bbms/1378314510. [24] Selmani, M., & Selmani, L. (2010). A frictional contact problem with wear and damage for electro-viscoelastic materials. Applications of Mathematics, 55, 89-109. Search In Google Scholar. https://doi.org/10.1007/s10492-010-0004-x [25] Sofonea, M., Han, W., & Shillor, M. (2005). Analysis and approximation of contact problems with adhesion or damage. Chapman and Hall/CRC. SEarch in Google Scholar. https://doi.org/10.1201/9781420034837 [26] Sofonea, M., Kazmi, K., Barboteu, M., & Han, W. (2012). Analysis and numerical solution of a piezoelectric frictional contact problem. Applied mathematical modelling, 36(9), 4483-4501. Search in Google Scholar. https://doi.org/10.1016/j.apm.2011.11.077 Communicated Editor: T.J. RABEHERIMANAN Manuscript received Sep. 19, 2024; revised Feb 02, 2025; accepted Feb 11, 2025; published Feb 28, 2025.